Racism in the Film The Help: Analysis of Narrative and Cinematographic Elements - Syarif Hidayat (STKIP PGRI Tulungagung, 2024)
Cinema or film had the power to depict societal realities, particularly those pertaining to social issues. The Help was one movie that uses narrative and cinematographic devices to depict social reality. In the movie The Help, a group of African-American domestic workers were the subject of unfair treatment and prejudice on the part of their white employers. This was due to the persistent perception that African Americans occupy an inferior status. In particular, Pettrie Boggs' (2018) narrative and cinematographic theories were used in this study, which employed qualitative methodologies and a structuralist approach. The goal of this study was to examine how narrative and cinematographic components in the movie The Help explore the topic of racial discrimination faced by African Americans in America. According to this study, the movie The Help contained narrative and cinematographic structural elements that illustrate racial inequality, most of which occured in the domestic setting. In addition, it was discovered that racial discrimination was not shown in movies in a compelling way. This appeared to be an attempt to simplify for the viewer the concept of racial prejudice as it was shown in the movie.